2016
DOI: 10.1039/c6ta01770c
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic substrates comprising gold nanostars efficiently regenerate cofactor molecules

Abstract: Gold nanostars as a photocatalyst perform better than rods and cubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 54 publications
1
36
0
Order By: Relevance
“…In particular, we will look at spherical NPs, NRs, and NSTs. The NSTs are especially interesting for the plasmonic effects since they have multiple hot spots at the tips . It was also shown experimentally and theoretically in refs.…”
Section: Electromagnetic Models Of Nanocrystals and Quantum Formalismmentioning
confidence: 71%
See 1 more Smart Citation
“…In particular, we will look at spherical NPs, NRs, and NSTs. The NSTs are especially interesting for the plasmonic effects since they have multiple hot spots at the tips . It was also shown experimentally and theoretically in refs.…”
Section: Electromagnetic Models Of Nanocrystals and Quantum Formalismmentioning
confidence: 71%
“…It was also shown experimentally and theoretically in refs. that the geometrical parameters of the tips in the NSTs strongly influence the positions of plasmonic resonances in such NCs. In our study, we first calculate classical optical properties of nanocrystals using the COMSOL software and the empirical dielectric constants of metals (gold and silver) .…”
Section: Electromagnetic Models Of Nanocrystals and Quantum Formalismmentioning
confidence: 99%
“…The first successful example of plasmonic cofactor photoregenerator was reported for gold nanorods coated with Pt domains on their tips (Figure 8B), thereby representing a previously defined plasmonic photocatalyst containing a heterojunction that combines a plasmonic structure (Au NRs) and a catalytic active site (Pt) to successfully carry out the regeneration (reduction) of NADH cofactor molecules [85]. A subsequent study carried out by the same authors determined an even more remarkable photo-response of gold nanostars with epitaxially grown Pt domains that was associated to the major light harvesting capacity of the star-shaped plasmonic structures (see Figure 8A) [84,85]. The potential combination of these plasmonic heterojunctions with other semiconductors represents a very promising alternative to obtain suitable mediators that can help to modulate multiple biochemical processes via light-induced inputs.…”
Section: Alternativementioning
confidence: 97%
“…A brief overview of the current state of the art in this field devoted to regular semiconductors has been recently published elsewhere [83].More recent studies involving the use of plasmonic materials have been reported by Sanchez-Iglesias et al Their studies focused on the evaluation of multiple gold-shaped plasmonic nanostructures (see Figure 8) and their effect on the effective photoregeneration of nicotinamide adenine dinucleotide (NADH) molecules. These latter molecules are extremely important in natural biochemical routes as mediating cofactors in many enzymes [84,85]. Moreover, cofactor molecules are necessary, for instance, in the photosynthesis process as light harvesters and intervening in the reduction-oxidation balances involved in respiration [86].…”
Section: Photobiocatalysismentioning
confidence: 99%
See 1 more Smart Citation